Hunger, an unfinished past: historiography, present time and inequality in Brazil (Tempo e Argumento, 2024)
The point of the article is that hunger is a fundamental feature of Brazilian republican history. To develop it, it aims to study the history of the fight against hunger in the country, with emphasis on the period which begins in 2014, when Brazil was left off the hunger map of the Food and Agriculture Organization of the United Nations (FAO). For the present text, studies from the field of History and historiography that discuss hunger; historical retrospectives of public policies to combat hunger in Brazil; and, finally, testimonials from representatives of the State and relevant social movements on this topic: Tereza Campello, former Minister of Social Development and Fight against Hunger; João Pedro Stédile, leader of the Movimento dos Trabalhadores Rurais Sem Terra (MST) and Rodrigo Afonso, CEO of Ação da Cidadania Contra a Fome.
Keywords: history of the fight against hunger in Brazil; history of health in Brazil; History of the present time